SWOT Analysis Factors Review of Waiting Time for Medical Record Services at Outpatient Registration at Community Health Centers Pulung, Ponorogo Regency - Ekky Febriyanti Putri; Dwi Nurjayanti (Institut Kesehatan Pelamonia, 2025)
This study aims to examine the factors influencing the waiting time in outpatient registration services of medical records at Pulung Public Health Center, Ponorogo Regency, using SWOT analysis (Strengths, Weaknesses, Opportunities, and Threats). The study employs a qualitative approach using interviews, observations, and documentation techniques. The results indicate that service strengths include basic facilities such as a waiting room, an electronic queuing system, and friendly staff behavior. However, weaknesses include a limited number of active registration officers, technical issues with SIMRS devices and printers, and suboptimal use of the electronic queue system. Opportunities for improvement include full digitalization of the medical record system and regular training for administrative staff. On the other hand, threats are high patient volumes, limited operational budgets, and technical disturbances due to unstable infrastructure. These findings highlight that efficient service is not solely dependent on technology but requires synergy between human resources, facilities, and information management. The SWOT analysis offers a strategic overview to help reduce waiting times and improve service quality. It is hoped that this research can serve as a basis for better policy formulation in managing medical record services at community health centers and act as a reference for future research.